Educational Level and Parenting Practices With Stunting Frequency Figures - Salva Alfinda Deviana Putri; Iriani Ismail (Edumaspul: Jurnal Pendidikan, 2023)
Optimal growth and development in the first 1000 days of life is important for every child. The level of education and parenting practices provided by parents are factors in the occurrence of stunting. Based on the latest data from the Indonesian Nutrition Status Survey (SSGI), the prevalence of stunting in East Java is quite high, reaching 19.2%.Bangkalan Regency is a district/city with a stunting prevalence rate that is still quite high, namely 26.2%. The aim of this research is to find out the relationship and influence of the level of education and parenting practices on the incidence of stunting.The highest prevalence of stunting in Bangkalan Regency is in Galis District with 166 cases. The sampling technique in this research used the Accidental Sampling technique, and the samples used were 33 samples. The analysis used in this research is bivariate analysis, multivariate analysis and the F test. This research uses a quantitative approach with data collection methods through questionnaires.The types of data used are primary and secondary data. Primary data is data obtained from the results of questionnaires that have been distributed, while secondary data is obtained from various kinds of literature and data in the relevant departments. The results of this research are: 1)The results of the chi-square test show that there is a relationship between education level and the incidence of stunting. 2) The results of the chi-square test also show that there is relationship between parenting practices and the incidence of stunting. 3) The results of multivariate analysis and the F test also show that the level of education and parenting practices of children simultaneously influence the incidence of stunting.